Improving Mathematical Comprehension and Communication Skills of High School Students through the Quantum Teaching Model - Farah Nurlia; Anizar Ahmad; Bansu Irianto Ansari, (International Journal of Scientific Research and Management (IJSRM), 2020)
The study aimed to investigate the improvement of the mathematical comprehension and communication skills of the students through learning the quantum teaching and conventional learning model. This research was an experimental study employing a pretest and posttest research design. The population of the study was all the Year 11 students from one of the senior high school in Banda Aceh, Indonesia, consisting of six classes. Two classes of samples were randomly selected, the experimental and the control classes. The instruments used in this research were a test of mathematical comprehension and communication skills. A statistical analysis employed to analyze the improvement of the mathematical comprehension and communication skills was t-test at the significance level of 0.005. The result showed that the improvement of the mathematical comprehension and communication skills of the students through the quantum teaching model was better than the conventional learning model. this study recommends that teachers implement quantum teaching models.